(untitled) (Research, Society and Development, 2022)
The present article has as a broader objective an analysis of the network to combat violence against women in the city of Teresina, capital of the State of Piauí, in order to present the design of the network with the equipment and services that operate in it - mainly involving the areas of Health, Public Security, Social Assistance and the Justice system - and the tensions between conceptions of violence, gender, family and care in disputes within them. Using a qualitative approach with multiple agents, actors and institutional actresses, the research was developed using different techniques: observation, document analysis, interviews and questionnaires. As main results, we highlight that, although structured in a network, the fight against violence against women in Teresina still suffers from difficulties regarding intersectoriality, transversality and capillarity, as it operates maintaining the classic and vertical structure of the institutions, with rigid competences, resulting in a “network” fragmented into micro-networks that sometimes operate in consonance, sometimes operate in a disconnected way and, in other cases, come into conflict. Associated with this, there are tensions between familist perspectives, present in some sectors (social assistance, public security and justice), and feminist and gender approaches that guide other sectors of the network, driven largely by feminist movements. Thus, there is a need to establish communicability protocols between institutions, standardization of referrals and the adoption of a more intersectional perspective in actions considering the cleavages of race and class in women’s lives.